Imipenem-Resistant Acinetobacter baumannii isolated from patients and hospitals environment in Baghdad - Hussein, Nadheema; Al-Mathkhury, Harith; Sabbah, Majeed (Iraqi Journal of Science, 2024)
During 2011, 1900 clinical specimens and 240 hospital environment specimens were collected from four hospitals in Baghdad. 128 isolates of Acinetobacter baumannii were obtained from clinical and environmental specimens in a percentage of 6.05% and 5.42%, respectively. The highest percentage of isolation, 83.62% was of sputum specimens and lower percentage of burns specimens 5.22%. The lowest incidence was of age range (71-80) years old group whereas the highest incidence was of age range (31-40) years old group. Also we found that the incidence was higher in males (66.96%) than that of females (33.04%) and the frequency of positive A. baumannii isolates was higher in intensive care units (ICUs). Results revealed eleven different resistotype patterns* designated arbitrarily from A-K and all our isolates showed multidrug resistance to those antibiotics. We found the highest percentage (85%) of imipenem resistant A. baumannii (IRAB) isolates were isolated from blood disease (leukemia) department followed by ICU, RCU, Burns, surgical and other departments, respectively.